Neuroprotective effects of Andrographolide extract in a Paraquat model of Parkinson’s disease and the possible role of Wnt signaling in the modulation of its anti-inflammatory and antioxidant propierties - (:unkn) unknown (My University, 2025)
Parkinson’s disease (PD) is a devastating worldwide neurodegenerative disorder which leads to several motor impairment and cognitive declination. Current therapies only provide symptomatic relief to PD symptoms, but no effective drugs are available to treat PD. Neuronal loss within the dopaminergic system and the formation of intracellular protein deposits, termed Lewy bodies, are at the basis of PD. Moreover, as observed in other neurodegenerative disorders, neuroinflammation, increased oxidative stress and mitochondrial dysfunction are part of the pathologic process that take place during PD. Although the etiology of PD is still unknown; environmental factors, such as exposure to chemical contaminants and air pollutants, among others, are considered as risk factors for PD presentation. Different pesticides, such as Paraquat, which are commonly used in the agriculture, including Chile, have been associated with parkinsonism. Moreover, several research groups, including our own, have determined the occurrence of PD hallmarks in pesticides-based PD models. In attention to these findings, several authors have proposed the pesticide-based models, as a reliable model for spontaneous PD and a useful tool in drug research against this disorder. Regrettably, the approach to PD has been focused on a few cellular pathways, but little is known about the involvement of additional central nervous system-relevant molecular pathways, such as the Wnt signaling, and especially about the Wnt-dependent mechanisms triggered during the environmental development of PD. Accordingly, the PD-related alteration of the Wnt signaling, as well as the impact of the crosstalk between the Wnt pathways and different molecular mechanisms related with PD-pathophysiology are unknown and are needed to be addressed in order to identify new potential therapeutical targets. Moreover, considering the urgent need of effective treatments against PD, as well as for other neurodegenerative disorders, the identification of new sources for drug research as well as new compounds, and its molecular mechanisms, is of most relevance. In this regard, it has been demonstrated that Andrographolide (ANDRO), extracted from Andrographis paniculata, exerts antioxidant and anti-inflammatory effects which prevent neurodegeneration in different Alzheimer’s disease models. Furthermore, it has been suggested that these effects are related with increased transcription of the Wnt target genes. Considering the high relevance of the inflammatory and oxidative stress processes in PD development, is of most interest to evaluate if the ANDRO extract can protects dopaminergic neurons against damaging insults, preventing the neuronal loss. Based in our experience with PD models, and the interesting properties already described for ANDRO, we hypothesize that the antioxidant and anti-inflammatory effects of ANDRO will be able to reduce the neuronal damage observed in a Paraquat-induced Parkinson’s disease-like model through the modulation of the canonical and no-canonical Wnt pathway. To evaluate the hypothesis, we propose (1) evaluate the modulation of Wnt signaling in the neuroprotective properties of ANDRO in an in vitro PQ-induced PD-like model; (2) evaluate the effects of ANDRO in the physiological parameters of an in vivo PQ-induced PD-like model; and (3) evaluate the modulation of Wnt signaling in the neuroprotective properties of ANDRO in an in vivo PQ-induced PD-like model. We believe that the data and the results obtained in this work will be very interesting and promising, regarding the utility of this molecule against PD. Additionally, this work should improve our knowledge about the molecular mechanisms involved in the development of this pathology.
Keywords: Parkinson's disease; Andrographolide; Alpha-synuclein; Pesticides